PENGARUH KEMAMPUAN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN LAHAT - Dinata, Febri; Kasinem; M.Pahlan (Journal of Economics and Development, 2025)
This study aims to determine how work ability and work experience partially and simultaneously influence employee performance at the Lahat Regency Civil Service Police and Fire Department. The sample size for this study was 91 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS software, resulting in a regression equation. The results of this study indicate a significant effect between work ability and employee performance at the Lahat Regency Civil Service Police and Fire Department. There is also a significant effect between work experience and employee performance at the Lahat Regency Civil Service Police and Fire Department. The F-test indicates that work ability and work experience simultaneously influence employee performance at the Lahat Regency Civil Service Police and Fire Department.